Application of the Discovery Learning Learning Model to Increase Student Learning Motivation in PPKN Class VII Subjects at SMP Negeri 12 Palu - Hidayat, Rais; Jamaludin, Jamaludin; Agusfitri, Dian (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the implementation of the discovery learning model in improving student learning motivation in Civics Education at SMP Negeri 12 Palu, specifically in class VII. The research employed a classroom action research (CAR) method, consisting of two cycles, each cycle involving planning, implementation, observation, and reflection. Data were collected through observations and interviews, which were then analyzed to measure changes in student learning motivation. The results showed that the implementation of the discovery learning model supported by technology could enhance student learning motivation. Significant improvements were observed in the indicators of student activity, persistence in tasks, and interest in the material, showing marked progress between cycle I and cycle II. Therefore, it can be concluded that the implementation of the discovery learning model, combined with technology, is effective in improving student learning motivation.